A Novel Hybrid Viabahn-assisted Bypass Technique: Extra-arterial Flossing Wiring for Chronic Total Occlusion in Superficial Femoral Artery. (2016) - Lin, T.C.; Chen, P.L.; Chen, I.M.
Abstract : Introduction: A hybrid Viabahn-assisted bypass (VAB) technique is introduced for revascularizing chronic total occlusion (CTO) in superficial femoral artery (SFA) when bypass surgery is difficult or endovascular intervention fails. Report: This technique combines extra-arterial flossing wiring with antegrade-retrograde intervention via traditional open exposure of middle SFA and deploying a Viabahn from the proximal true lumen through the subintimal lumen and extra-arterial space, and back into distal true lumen to restore flow. It only needs a 3–5 cm incision to expose the mid-SFA without clamping or endarterectomy of the SFA. Discussion: This hybrid procedure is an alternative technique to improve SFA revascularization in some difficult CTOs.